B-Side : Photography. Afropean. Fusion - Pitts, Johny; Prugnaud, Véronique; Marcilhacy, Vincent; Dahmani, Taous (S.l. : The Eyes Publishing, 2021)
Barnor, James ; Bonheur, Marvin ; Bourdeau, Rémy ; Boudjelal, Bruno ; Bourouissa, Mohamed ; Frantz, Anaïk ; Grant, Jazz ; Jafa, Arthur ; Jasse, Délio ; Johnson Artur, Liz ; Ndebele, Claudia ; Otchere, Eddie ; Pitts, Johny ; Rezaire, Tabita ; Yala Rodrigues, Sofia ; Rosi, Silvia ; Scheidig, Cédrine ; Sulter, Maud
boek